Perbedaan Persepsi Remaja Mengenai Pernikahan Dini Sebelum dan Sesudah Diberi Edukasi Dampak Pernikahan Dini Dengan Pendekatan Health Belief Model Di MA Miftahul Ulum Kalisat - Arzumni, Firyal Alifia; Palupi, Jenie; Susilawati, Susilawati (Jember Maternal and Child Health Journal; Vol 1 No 1 (2024): Jember Maternal and Child Health JournalDO - 10.31290/jmch.v1i1.4419, 2024)
Indonesia's early marriage is ranked seventh in the world. Whereas for the Jember area there are 962 marriage dispensation decisions for children under the age of 19 in 2021. The immature age of youth makes mothers unprepared during pregnancy, childbirth, and child care. As well as their reproductive organs and mental maturity that are not ready. This can increase the high maternal mortality rate (MMR), infant mortality rate (IMR), stunting, divorce and domestic violence (KDRT). This study aims to analyze differences in adolescent perceptions before and after being given education on the impact of early marriage using the Health Belief Model approach. Methods: The design in this study used one group pre test and post test. The sampling technique uses simple random sampling. The statistical analysis technique used in this study was the paired t-test. Results: There is a positive perception before being given education 79.49%, and the perception of youth after education is 89.745. With the Paired T-Test analysis, the results obtained were p <= 0.05 (0.004) where the null hypothesis was rejected or the research hypothesis was accepted or there were differences in adolescent perceptions of early marriage before and after being given education on the impact of early marriage using the Health Belief Model approach. Conclusion: Providing education with the Health Belief Model approach for adolescents can increase positive perceptions of the impact of early marriage so that adolescent perceptions are sure not to choose early marriage and choose to continue higher education